Evidence Based Medicine: Use of Probiotics in Pediatric Population for Diarrhoea. - MSA, Majid (Indian Journal of Pharmacy Practice)
Diarrhoea is the most common problem in pediatric population. Different causes and types of diarrhoea has been identified, i.e., diarrhoea during antibiotic treatment, non rota virus diarrhoea, or based on severity of diarrhoea like mild, moderate and severe form of diarrhoea. Several drugs like loperamide can be used but due to its side effects like stomach ache and bloating, drowsiness, constipation, etc use of these drugs has been limited. Probiotics- live microorganisms has also shown effective results in treatment of diarrhoea in pediatric population. Several types of probiotics are available that showed effective results. Evidence Based Medicine is the proof for drugs that can be used safely and for it several research works have been performed. Probiotics, in the same way, has been tested in different forms (Eg: Lactobacillus rhamnosus, Saccharomyces boulardii; Bacillus clausii, etc.) and has shown evidently that they can be safely administered at several doses for the treatment of different types or forms of diarrhoea in pediatrics.
Keywords: EBM; Diarrhoea; Pediatric; Probiotics